Behavioral and Electrophysiological Assessment of Adults Who Underwent Cochlear Implantation After Hearing Aid Experience - Calderaro, Victor Goiris; Amaral, Maria Stella Arantes do; Luz, Benedita Aparecida Borges da; Bernal, Sarah Carolina; Hyppolito, Miguel Ângelo; Reis, Ana Claudia Mirândola Barbosa (International Archives of Otorhinolaryngology, 2020)
Introduction Cochlear implantation has been considered a viable option to restore hearing perception in adults with severe to profound postlingual hearing loss.Objectives To analyze behavioral hearing responses and P300 latency and amplitude measurements in adults with bilateral sensorineural hearing loss at two phases, first when they were using hearing aids (HAs) and, then, after 12 months of cochlear implant (CI) use. The association between behavioral and electrophysiological evaluations was explored, as it is believed that the study of auditory processing with different hearing devices can contribute to future CI adjustments and fittings, especially for patients who cannot give subjective feedback (such as small children and individuals with multiple disabilities).Methods Prospective comparative study (Ethical approval 11489/2014). Twelve adults were assessed, 7 males and 5 females, in the 22 to 76 years old age range, who had undergone CI surgery after HA experience.Results The analyses showed an improvement of hearing thresholds when patients started using CIs. Comparing data from P300 latency measurements, there was an increase of the P300 wave post-CI at Cz and Fz. Regarding the amplitude, P300 mean values decreased at Cz, but increased at Fz. There was no significant correlation between behavioral and electrophysiological assessment and the variables age, gender, auditory deprivation, and electronic device used.Conclusion There was a significant improvement of hearing thresholds after twelve months of CI experience. The mean latency values of P300 after 12 months of CI use increased at Cz and Fz, while mean amplitude values decreased at Cz and increased at Fz.
Keywords: event-related potentials; P300; cochlear implantation; adult; hearing loss